Digitalization, Maritime Risk Management and Insurance Reforms in Developing Countries (Journal of Advances and Scholarly Researches in Allied Education, 2026)
The maritime sector remains the backbone of international trade, carrying nearly 80–90 percent of global merchandise by volume. Developing countries, particularly across South Asia, Southeast Asia, Africa, and Latin America, rely heavily on maritime transport for economic growth, energy security, and integration into global supply chains. However, these regions continue to face significant challenges in maritime safety, risk management, environmental protection, and insurance regulation. The rapid digitalization of shipping through electronic navigation systems, blockchain-enabled documentation, automated vessels, satellite tracking, and artificial intelligence-based predictive analytics has transformed maritime risk profiles. While digital tools enhance operational efficiency and safety, they also introduce cyber risks, systemic vulnerabilities, and regulatory complexities.This article examines the evolution of maritime risk management in developing regions through the lens of digital transformation and insurance reforms. It traces the historical development of maritime safety governance, the emergence of marine insurance as a risk-spreading mechanism, and the integration of digital technologies into shipping operations. A regional comparative approach highlights differences and similarities in regulatory preparedness, digital infrastructure, cyber risk management, and insurance market maturity across South Asia, Southeast Asia, Africa, and Latin America. The article further analyses international frameworks guiding maritime digitalization and insurance reform, including conventions developed under the International Maritime Organization and global best practices in marine insurance.The study argues that digitalization must be accompanied by coordinated insurance reforms, regulatory harmonization, capacity building, and cyber resilience strategies to ensure sustainable maritime development. It concludes that developing countries must integrate technological innovation with institutional reforms to strengthen safety at sea and reduce systemic maritime risks.